Pengembangan Media Pembelajaran Scratch untuk Materi Cerita Fantasi: Sebuah Tinjauan Umum - Indana Zulfa Rommadonia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The use of technology in learning has become a major focus in improving the effectiveness of the educational process. One promising tool is Scratch, a visual programming environment specifically designed for education. In the context of fantasy story learning, Scratch offers great potential to enhance students' creativity and engagement. This article provides an overview of Scratch-based learning media development for fantasy story materials. Through a literature review and analysis of related literature, the article identifies the advantages of using Scratch in fantasy story learning, such as increasing student engagement, developing problem-solving skills, and improving understanding of story concepts. In addition, it discusses the practical steps in developing Scratch learning media, including story concept selection, interactive design, and evaluation of learning outcomes. Thus, this study provides useful guidance for educators in developing interesting and effective learning media for fantasy story materials using Scratch.